Method for screening strontium potassium niobate ceramic with high spontaneous polarization intensity

By constructing a structural model of strontium potassium niobate ceramic unit cell with aerobic vacancy and cationic vacancy, and using the first principle to calculate its spontaneous polarization intensity, the problem of difficult screening of strontium potassium niobate ceramics in the prior art is solved, and the effect of significantly improving the spontaneous polarization intensity is achieved.

CN119626400AActive Publication Date: 2025-03-14河南省科学院半导体研究所

Patent Information

Application Number
CN202411659850.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-20
Publication Date
2025-03-14
Estimated Expiration
2044-11-20

AI Technical Summary

Technical Problem

It is difficult to effectively screen out strontium potassium niobate ceramics with high spontaneous polarization strength, especially during high-temperature sintering, elements such as K+ and Sr2+ are easily evaporated, resulting in the generation of oxygen vacancies and affecting the spontaneous polarization properties of the material.

Method used

By constructing a unit cell structure model of strontium potassium niobate ceramics present in oxygen vacancies, A-position cation vacancies and oxygen vacancies, B-position cation vacancies and oxygen vacancies, their spontaneous polarization strength was calculated using the first principle, and material components with high spontaneous polarization strength were screened out.

Benefits of technology

The efficient screening of strontium potassium niobate ceramics was achieved, which significantly improved its spontaneous polarization strength, specifically manifested as the spontaneous polarization strength of KSN-Nb1&O reached 56.39μC/cm2, which is 1.637 times that of pure KSN, and the calculation results are more accurate and in line with the actual situation.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119626400A_ABST
    Figure CN119626400A_ABST
Patent Text Reader

Abstract

The invention discloses a method for screening strontium potassium niobate ceramics with high spontaneous polarization intensity, which comprises the following steps: introducing oxygen vacancy, A-site cation (K + and Sr < 2 + >) vacancy and B-site cation (Nb15 + and Nb25 +) vacancy structures by considering that K < + >, Sr < 2 + > and a small amount of Nb5 < + > are easy to volatilize when KSN is sintered at a high temperature and along with the generation of oxygen vacancy, and calculating the oxygen vacancy according to a first principle calculation thought; the strontium potassium niobate ceramic with high spontaneous polarization intensity is screened according to the spontaneous polarization intensity of strontium potassium niobate existing in A-site cation vacancy (K < + > vacancy and Sr < 2 + > vacancy) and oxygen vacancy and B-site cation vacancy (Nb5 < + > vacancy) and oxygen vacancy; a first principle method is adopted for theoretical calculation, the strontium potassium niobate material component with high spontaneous polarization intensity is theoretically screened out, on-demand design is achieved, the research and development period is shortened, theoretical guidance is provided for actual experiments, and the experiment time and cost are saved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of oxide ceramics, and in particular relates to a method for screening potassium strontium niobate ceramics with high spontaneous polarization intensity. Background Art

[0002] Ferroelectric materials are materials that have spontaneous polarization that changes with an external electric field within a certain temperature range. Inside the ferroelectric material, the electric dipole moment is generated due to the offset of the positive and negative charge centers, resulting in spontaneous polarization inside the crystal. The polarization intensity is an important physical quantity to measure its ferroelectric properties. Its macroscopic electrical properties such as dielectric constant and conductivity are related to the spontaneous polarization intensity at the unit cell scale. Ferroelectric materials play an important role in the preparation and research of new components such as ferroelectric memory, pyroelectricity, pyroelectricity, ferroelectricity, electro-optical effect, acousto-optic effect, photorefractive effect and nonlinear optical effect due to their unique dielectric, piezoelectric, pyroelectric, ferroelectricity, and excellent properties such as electro-optical effect, acousto-optic effect, photorefractive effect and nonlinear optical effect.

[0003] Lead-free ferroelectric ceramics not only have satisfactory performance, but also do not contain lead and other substances that may cause damage to the ecological environment, humans and organisms, and have good development prospects. In particular, lead-free ferroelectric ceramics with tungsten bronze structure have attracted more and more attention, among which niobate crystal potassium strontium niobate (KSr2Nb5O 15 , referred to as KSN) material, because of its obvious optical birefringence effect, strong spontaneous polarization and high electro-optic coefficient, it has good application potential in optoelectronics, ferroelectrics and dielectrics, and can be used to manufacture surface acoustic wave filters, oscillators, temperature compensators and photocatalysis and other electronic components. Since the spontaneous polarization of most displacement ferroelectrics is caused by the distortion of oxygen octahedrons, the central atom deviates from its central symmetric position, and the dipole moment increases, that is, the influence of intrinsic defects and non-intrinsic defects on the electrical properties of materials is also reflected through the microscopic polarization intensity. Therefore, the central atom of the octahedron plays a vital role in the polarization of ferroelectrics. For KSN with a tungsten bronze structure, it is very necessary to study the influence of the central atom of the oxygen octahedron on polarization. Among them, introducing appropriate cation vacancies and oxygen vacancies to form defect dipoles, increase the induced dipole moment and spontaneous polarization intensity, and improve the dielectric constant of the material, thereby improving the spontaneous polarization intensity of ferroelectric materials is a feasible method to improve its ferroelectric properties.

[0004] In DOI: 10.1016 / j.physb.2021.413038, Qian Chen et al. published "Spontaneous electric polarization of high-valance-ion-doped lead-free ferroelectric KSr2Nb5O 15In this paper, the high-valent cation La was studied by first-principles calculations. 3+ ,Bi 3+ ,Y 3+ ,Ti 4+ ,Ta 5+ and W 6+ Doped KSr2Nb5O 15 The spontaneous polarization intensity of the doped KSr2Nb5O 15 The polarization strength of KSN was improved. However, the literature only studied the effect of cation doping substitution on the spontaneous polarization strength of KSN from the perspective of theoretical research. In the actual experimental process, KSN was sintered at high temperature. + and Sr 2+ And a small amount of Nb 5+ It is easy to volatilize, and accompanied by the generation of oxygen vacancies, the model established in the literature cannot better reflect the actual situation. At the same time, the cross-correlation pseudopotential selected in the calculation process of the literature to optimize the unit cell structure is LDA (CA-PZ), and the unit cell volume of the optimized KSN is The unit cell volume of KSN in the PDF card The difference is quite large. Since the gap between the optimized unit cell structure and the real unit cell volume of the structure has a great influence on the stability and performance of the material system, it is necessary to choose a more appropriate pseudopotential to obtain a crystal structure that better matches the real structure.

[0005] In DOI: 10.1002 / pssb.202100488, Qian Chen et al. published "Effect of intrinsic Nb 5+ vacancy on dielectric and polarization behaviors of KSr2Nb5O 15 :first-principles investigation". In this paper, first-principles calculations were used to study the 5+ The influence of vacancies on the spontaneous polarization behavior of KSN. However, the unit cell model established in this paper is only based on theoretical research, and the established model is still lacking in studying the influence of vacancy defects on the spontaneous polarization intensity of KSN in the actual experimental process. At the same time, the unit cell volume optimized by the cross-correlation pseudopotential LDA (CA-PZ) in the paper is quite different from that in the PDF card, and it is necessary to select a more suitable pseudopotential to optimize the unit cell structure.

[0006] The macroscopic polarization intensity of KSN bulk materials can be obtained by testing hysteresis loops, but the spontaneous polarization intensity at the unit cell scale is difficult to measure experimentally and needs to be obtained through calculations using first-principles methods to further understand the intrinsic relationship between intrinsic defects and non-intrinsic defects, microscopic polarization intensity and macroscopic polarization intensity. Summary of the invention

[0007] In order to overcome the above-mentioned shortcomings of the prior art, the object of the present invention is to provide a method for screening potassium strontium niobate ceramics with high spontaneous polarization strength, by considering the KSN under high temperature sintering K + and Sr 2+ And a small amount of Nb 5+ It is easy to volatilize, and at the same time, oxygen vacancies are generated, and oxygen vacancies, A-site cations (K + and Sr 2+ ) vacancies and B-site cations (Nb1 5+ and Nb2 5+ ) vacancy structure, based on the first principle calculation idea, the oxygen vacancy, A-site cation vacancy (K + Vacancy, Sr 2+ vacancies) and oxygen vacancies, B-site cation vacancies (Nb 5+ The spontaneous polarization intensity of potassium strontium niobate with the presence of vacancies (such as carbon vacancies) and oxygen vacancies was studied, and potassium strontium niobate ceramics with high spontaneous polarization intensity were screened out.

[0008] In order to achieve the above-mentioned invention object, the technical solution adopted by the present invention is:

[0009] A method for screening potassium strontium niobate with high spontaneous polarization intensity comprises the following steps:

[0010] Step 1, construct KSr2Nb5O 15 The unit cell structure model is denoted as KSN, and its unit cell structure is ordered;

[0011] Step 2, based on the ordered KSr2Nb5O in step 1 15 The unit cell structure of KSr2Nb5O with oxygen vacancies, cation vacancies and oxygen vacancies at A sites, and cation vacancies and oxygen vacancies at B sites is constructed. 15 The unit cell structure models are denoted as KSN-O, KSN-K&O, KSN-Sr&O, KSN-Nb1&O, and KSN-Nb2&O;

[0012] Step 3, using VASPKIT software to perform convergence tests on the KSN obtained in step 1 and the KSN-O, KSN-K&O, KSN-Sr&O, KSN-Nb1&O and KSN-Nb2&O obtained in step 2, respectively, to determine the calculation parameters when the system reaches convergence;

[0013] Step 4, based on the calculation parameters when the system reaches convergence in step 3, use CASTEP software to optimize the KSN obtained in step 1 and the KSN-O, KSN-K&O, KSN-Sr&O, KSN-Nb1&O and KSN-Nb2&O unit cell structures obtained in step 2, respectively, so as to achieve the lowest energy of the system and obtain the most stable unit cell structure;

[0014] Step 5, using CASTEP software to calculate the optical frequency dielectric constants of the most stable KSN, KSN-O, KSN-K&O, KSN-Sr&O, KSN-Nb1&O and KSN-Nb2&O unit cell structures in step 4 respectively;

[0015] Step 6, based on the Clausius-Mossotti equation, calculate the ionic polarizabilities of the most stable KSN, KSN-O, KSN-K&O, KSN-Sr&O, KSN-Nb1&O and KSN-Nb2&O unit cell structures in step 4 respectively;

[0016] Step 7, calculating the spontaneous polarization intensity range of the KSN unit cell structure according to the ionic polarizability of the KSN unit cell structure obtained in step 6;

[0017] Step 8, according to step 7, the spontaneous polarization intensity range of KSN is obtained, the built-in electric field range is calculated, and then according to the relationship between the spontaneous polarization intensity and the built-in electric field, the spontaneous polarization intensity of the most stable KSN-O, KSN-K&O, KSN-Sr&O, KSN-Nb1&O and KSN-Nb2&O unit cell structures in step 4 is obtained;

[0018] Step 9: Based on the spontaneous polarization intensity ranges of the KSN-O, KSN-K&O, KSN-Sr&O, KSN-Nb1&O and KSN-Nb2&O unit cell structures obtained in step 8, potassium strontium niobate ceramics with high spontaneous polarization intensity are screened out.

[0019] In step 2, KSr2Nb5O with oxygen vacancies, cation vacancies and oxygen vacancies at site A, and cation vacancies and oxygen vacancies at site B is constructed. 15 The unit cell structure model process is as follows:

[0020] Delete KSr2Nb5O 15 One O atom in the unit cell structure corresponds to a vacancy concentration of 2.17 atom%, resulting in K2Sr4Nb 10 O 29 The unit cell structure is denoted as KSN-O;

[0021] Delete KSr2Nb5O 15There is one K atom and one O atom in the unit cell structure, and the corresponding vacancy concentration is 4.35 atom%, resulting in KSr4Nb 10 O 29 The unit cell structure is denoted as KSN-K&O;

[0022] Delete KSr2Nb5O 15 There is one Sr atom and one O atom in the unit cell structure, and the corresponding vacancy concentration is 4.35 atom%, resulting in K2Sr3Nb 10 O 29 The unit cell structure is denoted as KSN-Sr&O;

[0023] Delete KSr2Nb5O 15 The Nb atoms and O atoms located at the Nb1 position in the unit cell structure have a corresponding vacancy concentration of 4.35 atom%, resulting in K2Sr4Nb9O 29 The unit cell structure is denoted as KSN-Nb1&O;

[0024] Delete KSr2Nb5O 15 The Nb atoms and O atoms located at the Nb2 position in the unit cell structure have a corresponding vacancy concentration of 4.35 atom%, resulting in K2Sr4Nb9O 29 The unit cell structure is denoted as KSN-Nb2&O.

[0025] 3. A method for screening potassium strontium niobate with high spontaneous polarization intensity according to claim 1, characterized in that in step 3, the KSN obtained in step 1 and the KSN-O, KSN-K&O, KSN-Sr&O, KSN-Nb1&O and KSN-Nb2&O obtained in step 2 are tested for convergence by using the PBE pseudopotential library in the VASPKIT software to determine that the cutoff energy is 750 eV, the k-point is 6×6×6, and the energy convergence standard is 4.0×10 -5 eV, the convergence criterion for the force is that a single atom is below The maximum displacement is

[0026] The process of calculating the ion polarizability based on the Clausius-Mossotti equation in step 6 is as follows:

[0027] The expression of the Clausius-Mossotti equation is as follows:

[0028]

[0029] Among them, ε r represents the relative dielectric constant, ε0 represents the vacuum dielectric constant, 8.85×10 -12 F / m, α represents the ionic polarizability, and n0 represents the number of polarized particles per unit volume of the dielectric;

[0030] If the volume is replaced by the molar volume M / ρ, then:

[0031]

[0032] Where N0 is Avogadro's constant, in mol -1 , M represents the molar mass of the dielectric, and ρ represents the density;

[0033] because

[0034] Where V is the unit cell volume;

[0035] Substituting formula (3) into the transformation of formula (2): get:

[0036]

[0037] At optical frequencies, the relative dielectric constant ε of a dielectric is r Available optical frequency dielectric constant ε ∞ To express, at this time, formula (1) can be expressed as:

[0038]

[0039] According to the optical frequency dielectric constant ε calculated from the first principles in step 5 ∞ , the product n0α of the number of polarized particles n0 per unit volume of the material and the ionic polarizability α is calculated using formula (5); and the number of polarized particles n0 per unit volume is obtained by formula (4), and then the ionic polarizability α is obtained.

[0040] The process of calculating the spontaneous polarization intensity range of the KSN unit cell structure in step 7 is as follows:

[0041] Step 7.1: Calculate the dipole moment of KSN by experimental method and first principles, namely:

[0042] Method 1: Calculate the dipole moment of KSN according to the experimental method:

[0043] Curie temperature T of KSN obtained by experimental method c , get Nb in KSN 5+ The offset △z of KSN is obtained, and then the dipole moment of KSN is obtained;

[0044] The displacement △z of the cation offset charge center in the displacement type ferroelectric unit cell is related to the Curie temperature T c The relationship is as follows:

[0045] T C =2×10 4(Δz) 2 (6)

[0046] Among them, T c Represents Curie temperature, in K;

[0047] The relationship between the displacement △z of the cation offset charge center in the displacement-type ferroelectric unit cell and the dipole moment of KSN is as follows:

[0048] μ KSN =nqΔz (7)

[0049] Among them, μ KSN represents the dipole moment of KSN, in C·m; n represents the number of atoms; q represents the unit charge, 1.6×10 -19 C;

[0050] Method 2: Calculate the dipole moment of KSN based on first principles:

[0051] The most stable KSN unit cell structure obtained in step 4 is input into the VASP software to obtain the average distance l between positive and negative charges. The dipole moment of KSN is calculated based on the first principles, and the expression is as follows:

[0052] μ KSN =nql (8)

[0053] Among them, μ KSN represents the dipole moment of KSN, in C·m; n represents the number of atoms; l represents the average distance between positive and negative charges; q represents the unit charge, 1.6×10 -19 C;

[0054] Step 7.2: Calculate the spontaneous polarization intensity range of KSN based on the dipole moment of KSN obtained in step 7.1;

[0055] The two expressions of the spontaneous polarization intensity are as follows:

[0056]

[0057] Where μ represents the dipole moment and V represents the unit cell volume;

[0058] P=n0μ=n0αE e (10)

[0059] Where n0 represents the number of polarized particles per unit volume of the dielectric; μ represents the dipole moment; α represents the ionic polarizability; E e represents the built-in electric field;

[0060] Substitute the dipole moment of KSN obtained by experimental method and first-principles calculation in step 7.1 into equations (9) and (10) respectively to obtain the spontaneous polarization intensity range of KSN.

[0061] The chemical composition of potassium strontium niobate ceramics with high spontaneous polarization intensity selected in step 9 is: K2Sr4Nb 10 O 29 、KSr4Nb 10 O 29 and K2Sr4Nb9O 29 .

[0062] Compared with the existing technology, the beneficial effects achieved by the present invention are:

[0063] 1. The present invention introduces oxygen vacancies, A-site cations (K + and Sr 2+ ) vacancies and B-site cations (Nb1 5+ and Nb2 5 + ) vacancy structure, introducing a greater degree of lattice distortion, and a greater distance from the center position of the Nb-O octahedron, causing a greater spontaneous polarization intensity; at the same time, the spontaneous polarization intensity of potassium strontium niobate ceramics with oxygen vacancies, A-site cation vacancies and oxygen vacancies, as well as B-site cation vacancies and oxygen vacancies were calculated according to the first principles, and the potassium strontium niobate material components with higher spontaneous polarization intensity were screened out, that is, the spontaneous polarization intensity of potassium strontium niobate material satisfies KSN-Nb1&O>KSN-O>KSN-K&O>KSN-Nb2&O>KSN-Sr&O.

[0064] 2. In the prior art, when VASP is used to calculate the dipole moment of an insulating system containing doping and vacancies, the system will easily default to conductor processing, causing the calculation results to deviate from the actual situation. The results of the present invention confirm the dipole moment and spontaneous polarization intensity range of the defective system through the dipole moment and spontaneous polarization intensity range of the defective KSN, which is in line with the actual situation and can obtain more accurate spontaneous polarization intensity results.

[0065] 3. Compared with the LDA pseudopotential library used in the prior art, the present invention adopts the electronic structure information of the corresponding atoms in the PBE pseudopotential library in the process of determining the calculation parameters when the system reaches convergence in step 3, which is more suitable for the unit cell system structure with defects. The calculation results of the spontaneous polarization intensity are more accurate, and the whole process is simple in calculation, easy to operate and has a short R&D cycle.

[0066] In summary, the present invention constructs oxygen vacancies, A-site cations (K + ,Sr 2+ ) vacancies and oxygen vacancies as well as B-site cations (Nb15+ and Nb2 5+ ) vacancies and oxygen vacancies in potassium strontium niobate unit cell structure, and use the first principle to calculate its optical frequency dielectric properties, and then use the Clausius-Mossotti equation to obtain its ionic polarizability. Then, the dipole moment and spontaneous polarization intensity of KSN are calculated from the ionic polarizability of KSN, and the spontaneous polarization intensity of defects is determined. Finally, the potassium strontium niobate material component with higher spontaneous polarization intensity is screened out, that is, KSN-Nb1&O has the highest spontaneous polarization intensity, reaching 56.39μC / cm 2 , is the spontaneous polarization intensity of pure KSN (34.45μC / cm 2 ) and is 1.637 times higher than the spontaneous polarization intensity of KSN single crystal reported in the literature (25 μC / cm 2 ) is 2.256 times; the present invention adopts the first-principles method to perform theoretical calculations and theoretically screens out potassium strontium niobate material components with high spontaneous polarization intensity, thereby realizing on-demand design, shortening the research and development cycle, providing theoretical guidance for actual experiments, and saving experimental time and cost. BRIEF DESCRIPTION OF THE DRAWINGS

[0067] Figure 1 is a unit cell structure diagram of the present invention, wherein, Figure 1 (a) is KSN, Figure 1 (b) is KSN-O, Figure 1 (c) KSN-K&O, Figure 1 (d) is KSN-Sr&O, Figure 1 (e) is KSN-Nb1&O, Figure 1 (f) is KSN-Nb2&O.

[0068] Figure 2 It is the optical frequency dielectric constant of KSN, KSN-O, KSN-K&O, KSN-Sr&O, KSN-Nb1&O and KSN-Nb2&O of the present invention.

[0069] Figure 3 It is the ionic polarizability of KSN, KSN-O, KSN-K&O, KSN-Sr&O, KSN-Nb1&O and KSN-Nb2&O of the present invention.

[0070] Figure 4 It is the spontaneous polarization intensity of KSN, KSN-O, KSN-K&O, KSN-Sr&O, KSN-Nb1&O and KSN-Nb2&O of the present invention. DETAILED DESCRIPTION

[0071] The technical solution of the present invention is further described below in conjunction with the accompanying drawings.

[0072] A method for screening potassium strontium niobate with high spontaneous polarization strength, by calculating the spontaneous polarization strength of potassium strontium niobate with oxygen vacancies, A-site cation vacancies and oxygen vacancies, and B-site cation vacancies and oxygen vacancies, to screen out potassium strontium niobate ceramics with high spontaneous polarization strength, wherein the chemical composition of the potassium strontium niobate with high spontaneous polarization strength is: K2Sr4Nb 10 O 29 、KSr4Nb 10 O 29 and K2Sr4Nb9O 29 ; The specific process is as follows:

[0073] Step 1, construct KSr2Nb5O 15 The unit cell structure model is recorded as KSN, and its unit cell structure is ordered. The specific process is as follows:

[0074] First, the unit cell structure model of perfect KSN is established. The unit cell structure model of KSN (Code95741) is derived from the ICSD database and ordered. 2+ and K + All with Sr 2+ Instead, Sr in the four directions 2+ Use K + Instead, satisfy KSr2Nb5O 15 The stoichiometric ratio of KSr2Nb5O 15 Ordering of the unit cell structure;

[0075] Step 2, based on the ordered KSr2Nb5O in step 1 15 The unit cell structure of KSr2Nb5O with oxygen vacancies, cation vacancies and oxygen vacancies at A sites, and cation vacancies and oxygen vacancies at B sites is constructed. 15 Unit cell structure model, the specific process is as follows:

[0076] like Figure 1 As shown, KSr2Nb5O is deleted 15 One O atom in the unit cell structure corresponds to a vacancy concentration of 2.17 atom%, resulting in K2Sr4Nb 10 O 29 The unit cell structure is denoted as KSN-O;

[0077] Delete KSr2Nb5O 15 There is one K atom and one O atom in the unit cell structure, and the corresponding vacancy concentration is 4.35 atom%, resulting in KSr4Nb 10 O 29 The unit cell structure is denoted as KSN-K&O;

[0078] Delete KSr2Nb5O 15There is one Sr atom and one O atom in the unit cell structure, and the corresponding vacancy concentration is 4.35 atom%, resulting in K2Sr3Nb 10 O 29 The unit cell structure is denoted as KSN-Sr&O;

[0079] Since the number of atoms around the two Nb species and the distances from the surrounding atoms are different, the spontaneous polarization intensities of the B-site cation vacancy and the O vacancy need to be considered separately; 15 The Nb atoms and O atoms located at the Nb1 position in the unit cell structure have a corresponding vacancy concentration of 4.35 atom%, resulting in K2Sr4Nb9O 29 The unit cell structure is denoted as KSN-Nb1&O;

[0080] Delete KSr2Nb5O 15 The Nb atoms and O atoms located at the Nb2 position in the unit cell structure have a corresponding vacancy concentration of 4.35 atom%, resulting in K2Sr4Nb9O 29 The unit cell structure is denoted as KSN-Nb2&O;

[0081] Step 3: Use VASPKIT software to perform convergence tests on the KSN obtained in step 1 and the KSN-O, KSN-K&O, KSN-Sr&O, KSN-Nb1&O, and KSN-Nb2&O obtained in step 2 to determine the calculation parameters when the system reaches convergence; the specific process is as follows:

[0082] The PBE pseudopotential library was used in the VASPKIT software to perform convergence tests on the KSN obtained in step 1 and the KSN-O, KSN-K&O, KSN-Sr&O, KSN-Nb1&O, and KSN-Nb2&O obtained in step 2. The cutoff energy was determined to be 750 eV, the k-point was 6×6×6, and the energy convergence criterion was 4.0×10 -5 eV, the convergence criterion for the force is that a single atom is below The maximum displacement is The PBE functional theory under the generalized gradient approximation GGA is selected to explain the interaction between electrons, and the electronic structure information of the corresponding atoms in the PBE pseudopotential library is called; the PBE functional has high accuracy in describing the electron correlation effect, can better predict the physical properties of materials, such as lattice constants, etc., and can be widely applied to a variety of material systems, including metals, semiconductors, insulators and superconductors, etc. At the same time, the calculation cost is relatively low, which is suitable for the unit cell system structure containing defects this time;

[0083] Step 4, based on the calculation parameters when the system reaches convergence in step 3, the KSN obtained in step 1 and the KSN-O, KSN-K&O, KSN-Sr&O, KSN-Nb1&O and KSN-Nb2&O unit cell structures obtained in step 2 are optimized using CASTEP software to achieve the lowest energy of the system and obtain the most stable unit cell structure; the optimized unit cell volume is shown in Table 1;

[0084] Step 5, using CASTEP software to calculate the optical frequency dielectric constants of the most stable KSN, KSN-O, KSN-K&O, KSN-Sr&O, KSN-Nb1&O and KSN-Nb2&O unit cell structures in step 4 respectively; the specific process is as follows:

[0085] The optical frequency dielectric constants ε of the most stable KSN, KSN-O, KSN-K&O, KSN-Sr&O, KSN-Nb1&O and KSN-Nb2&O unit cell structures in step 4 were calculated using CASTEP software. ∞ , that is, check the Optical properties option in the Calculation window of the CASTEP software and perform the calculation; after the calculation is completed, the optical frequency dielectric constant ε is obtained in the result window ∞ , as shown in Table 1;

[0086] Step 6, based on the Clausius-Mossotti equation, calculate the ionic polarizabilities of the most stable KSN, KSN-O, KSN-K&O, KSN-Sr&O, KSN-Nb1&O and KSN-Nb2&O unit cell structures in step 4 respectively;

[0087] The expression of the Clausius-Mossotti equation is as follows:

[0088]

[0089] Among them, ε r represents the relative dielectric constant, ε0 represents the vacuum dielectric constant, 8.85×10 -12 F / m, α represents the ionic polarizability, and n0 represents the number of polarized particles per unit volume of the dielectric;

[0090] If the volume is replaced by the molar volume M / ρ, then:

[0091]

[0092] Where N0 is Avogadro's constant, in mol -1 , M represents the molar mass of the dielectric, and ρ represents the density;

[0093]

[0094] Where V represents the unit cell volume;

[0095] Substituting formula (3) into the transformation of formula (2): get:

[0096]

[0097] At optical frequencies, the relative dielectric constant ε of a dielectric is r Available optical frequency dielectric constant ε ∞ To express, at this time, formula (1) can be expressed as:

[0098]

[0099] According to the optical frequency dielectric constant ε calculated from the first principles in step 5 ∞ , the product n0α of the number of polarized particles n0 and the ionic polarizability α per unit volume of the material is calculated using formula (5); and the number of polarized particles n0 per unit volume is obtained by formula (4), and the ionic polarizability α is then obtained, as shown in Table 1;

[0100] Table 1 Ionic polarizability α of KSN, KSN-O, KSN-K&O, KSN-Sr&O, KSN-Nb1&O and KSN-Nb2&O

[0101]

[0102] Step 7, calculating the spontaneous polarization intensity range of the KSN unit cell structure according to the ionic polarizability of the KSN unit cell structure obtained in step 6;

[0103] Step 7.1: Calculate the dipole moment of KSN by experimental method and first principles, namely:

[0104] Method 1: Calculate the dipole moment of KSN according to the experimental method:

[0105] Studies have shown that (Zhang Liangying. Dielectric Physics [M]. Xi'an Jiaotong University Press, 1991.) the displacement of the cation charge center in the displacement ferroelectric unit cell is related to the Curie temperature T c The relationship is as follows:

[0106] T C =2×10 4 (Δz) 2 (6)

[0107] Among them, T c Curie temperature T c , unit is K;

[0108] Spontaneous polarization of KSN comes from Nb5+ The ion shifts along the

[001] direction to the center of the oxygen octahedron. The Curie temperature of KSN is 150 °C, i.e., 423 K. Substituting into the above formula (6), we can obtain Nb in KSN. 5+ The offset △z is Therefore, the dipole moment of KSN is:

[0109] μ KSN =nqΔz=10×5×1.6×10 -19 ×0.1454×10 -10 =11.632×10 -29 (7)

[0110] Among them, μ KSN represents the dipole moment of KSN, in C·m; n represents the number of atoms; q represents the unit charge, 1.6×10 -19 C;

[0111] Method 2: Calculate the dipole moment of KSN based on first principles:

[0112] The most stable KSN unit cell structure obtained in step 4 is input into the VASP software to obtain the average distance l between positive and negative charges. The dipole moment of KSN is calculated according to the first principles, and the expression is as follows:

[0113] μ KSN =nql=10×1.309×10 -10 ×1.6×10 -19 =20.951×10 -29 (8)

[0114] Among them, μ KSN represents the dipole moment of KSN, in C·m; n represents the number of atoms; l represents the average distance between positive and negative charges; q represents the unit charge, 1.6×10 -19 C;

[0115] Step 7.2: Calculate the spontaneous polarization intensity range of KSN based on the dipole moment of KSN obtained in step 7.1;

[0116] The spontaneous polarization intensity is defined as the vector sum of the molecular electric dipole moments per unit volume, which reflects the polarization degree of the dielectric and can be expressed by formula (9):

[0117]

[0118] Where μ represents the dipole moment and V represents the unit cell volume;

[0119] The spontaneous polarization intensity can also be expressed by formula (10):

[0120] P=n0μ=n0αEe (10)

[0121] Where n0 represents the number of polarized particles per unit volume of the dielectric; μ represents the dipole moment; α represents the ionic polarizability; E e represents the built-in electric field;

[0122] By KSN standard card PDF#34-0123, The unit cell volume Substituting the dipole moment of KSN obtained by the experimental method in step 7.1 into equation (9), we can obtain the spontaneous polarization intensity of KSN as 19.07 μC / cm 2 Substituting the dipole moment of KSN obtained by the experimental method in step 7.1 into equation (10), the spontaneous polarization intensity of KSN is obtained to be 19.12 μC / cm 2 ;

[0123] The unit cell volume of KSN obtained from the first-principles calculation in step 4 is Substituting the dipole moment of KSN obtained by first-principles calculation in step 7.1 into equation (9), we obtain the spontaneous polarization intensity of KSN to be 34.45 μC / cm 2 ; Substituting the dipole moment of KSN obtained by first-principles calculation in step 7.1 directly into equation (10), the spontaneous polarization intensity of KSN is obtained to be 34.44 μC / m 2 ;

[0124] Therefore, the spontaneous polarization intensity of KSN ranges from 19.07 to 34.45 μC / cm 2 , as shown in Table 2;

[0125] Step 8, according to step 7, the spontaneous polarization intensity range of KSN is obtained, the built-in electric field range is calculated, and then according to the relationship between the spontaneous polarization intensity and the built-in electric field, the spontaneous polarization intensity of the most stable KSN-O, KSN-K&O, KSN-Sr&O, KSN-Nb1&O and KSN-Nb2&O unit cell structures in step 4 is obtained;

[0126] Substituting the value of the product of the number of polarizable particles n0 and the ionic polarizability α per unit volume of the material in Table 1 into (10), the relationship between the spontaneous polarization intensity and the built-in electric field of KSN, KSN-O, KSN-K&O, KSN-Sr&O, KSN-Nb1&O and KSN-Nb2&O can be obtained as follows:

[0127] P KSN =13.979×10 -12 E e (11)

[0128] P KSN-O=19.805×10 -12 E e (12)

[0129] P KSN-K&O =19.110×10 -12 E e (13)

[0130] P KSN-Sr&O =12.664×10 -12 E e (14)

[0131] P KSN-Nb1&O =22.881×10 -12 E e (15)

[0132] P KSN-Nb2&O =16.245×10 -12 E e (16)

[0133] The unit of spontaneous polarization intensity P is

[0134] Substituting the spontaneous polarization intensity range of KSN obtained in step 7.2 into equation (11), we get the built-in electric field E e The range is 13.642-24.644 MV / mm; the built-in electric field E obtained in step 8 e Substituting the range of into equations (12)-(16), we can obtain the spontaneous polarization intensity ranges of KSN-O, KSN-K&O, KSN-Sr&O, KSN-Nb1&O and KSN-Nb2&O, as shown in Table 2. min Represents the minimum value of spontaneous polarization intensity, P max represents the maximum value of spontaneous polarization intensity, △P represents the change of spontaneous polarization intensity;

[0135] Step 9: Based on the spontaneous polarization intensity ranges of the KSN-O, KSN-K&O, KSN-Sr&O, KSN-Nb1&O and KSN-Nb2&O unit cell structures obtained in step 8, potassium strontium niobate ceramics with high spontaneous polarization intensity are screened out.

[0136] The spontaneous polarization intensity of KSN single crystal reported in the literature (RR Neurgaonkar, WK Cory, JR O liver, et al. Growth and optical properties of ferroelectric tungsten bronze crystals [J]. Ferroelectrics. 1993, 142: 167-188.) is 25 μC / cm 2 As an example, substituting into equation (10), we get the built-in electric field E e is 17.88 (MV / mm); the built-in electric field E e Substituting into equations (11)-(15), the spontaneous polarization intensities of KSN-O, KSN-K&O, KSN-Sr&O, KSN-Nb1&O and KSN-Nb2&O are obtained. As shown in Table 2, the calculated spontaneous polarization intensities are all within the range of the spontaneous polarization intensities obtained by the screening method of the present invention, which shows the rationality of the method;

[0137] Table 2 Spontaneous polarization intensity (μC / cm) of KSN, KSN-O, KSN-K&O, KSN-Sr&O, KSN-Nb1&O and KSN-Nb2&O 2 )

[0138]

[0139] Figure 1 The unit cell structure diagram of the present invention is as follows. When establishing the KSN-O structure with oxygen vacancies, one of the O atoms is deleted; + When KSN-K&O coexists with vacancies and oxygen vacancies, one K atom and one O atom are deleted; Sr 2+ When KSN-Sr&O contains vacancies and oxygen vacancies, one Sr atom and one O atom are deleted; Nb1 is established 5+ When KSN-Nb1&O coexists with vacancies and oxygen vacancies, delete one Nb atom and one O atom located at the Nb1 position; create Nb2 5+ In KSN-Nb1&O where vacancies and oxygen vacancies coexist, one Nb atom and one O atom located at the Nb1 position are deleted.

[0140] Figure 2 is the optical frequency dielectric constant of KSN, KSN-O, KSN-K&O, KSN-Sr&O, KSN-Nb1&O and KSN-Nb2&O of the present invention; the optical frequency dielectric constant ε of other structures with vacancies except KSN-Sr&O ∞ Compared with KSN, they have improved, which is mainly due to Sr 2+Vacancies and oxygen vacancies have the same charge but opposite electrical properties, so part of the interaction is offset, and the optical frequency dielectric constant decreases. Figure 2 It can be seen that the optical frequency dielectric constant of KSN-Nb1&O is the highest, which is 19.070, which is 4.4 times that of KSN (4.336). It is followed by the optical frequency dielectric constant of KSN-O (9.809), the optical frequency dielectric constant of KSN-K&O (8.750) and the optical frequency dielectric constant of KSN-Nb2&O (5.729).

[0141] Figure 3 It is the ionic polarizability of KSN, KSN-O, KSN-K&O, KSN-Sr&O, KSN-Nb1&O and KSN-Nb2&O of the present invention; when vacancies exist, except for KSN-Sr&O, the ionic polarizability of other materials is improved, among which the ionic polarizability of KSN-Nb1&O is the highest, which is 1.638 times of that of KSN, followed by KSN-O>KSN-K&O>KSN-Nb2&O>KSN-Sr&O; it can be seen that the presence of vacancies can effectively improve the ionic polarizability of KSN, especially KSN-Nb1&O.

[0142] Figure 4 is the spontaneous polarization intensity of KSN, KSN-O, KSN-K&O, KSN-Sr&O, KSN-Nb1&O and KSN-Nb2&O of the present invention, and the maximum value P of the spontaneous polarization intensity range is adopted. max For example, the blue area is the built-in electric field E e The spontaneous polarization intensity of each material ranges under the range. Except for KSN-Sr&O, the spontaneous polarization intensity of other vacancy systems is enhanced. Among them, KSN-Nb1&O has the highest spontaneous polarization intensity of 56.39μC / cm 2 , is the KSN spontaneous polarization intensity (34.45μC / cm 2 ) is 1.637 times of that of KSN-O; followed by the spontaneous polarization intensity of KSN-O, 48.81 μC / cm 2 The spontaneous polarization intensity of KSN-K&O is 47.09μC / cm 2 The spontaneous polarization intensity of KSN-Nb2&O is 40.03μC / cm 2 ; It can be seen that the presence of vacancies can effectively increase the spontaneous polarization intensity of KSN, especially the Nb 5+ When vacancies and oxygen vacancies coexist, the spontaneous polarization intensity is the highest.

Claims

1. A method for screening potassium strontium niobate with high spontaneous polarization intensity, characterized in that: The steps include: Step 1, construct KSr2Nb5O 15 The unit cell structure model is denoted as KSN, and its unit cell structure is ordered; Step 2, based on the ordered KSr2Nb5O in step 1 15 The unit cell structure of KSr2Nb5O with oxygen vacancies, cation vacancies and oxygen vacancies at A sites, and cation vacancies and oxygen vacancies at B sites is constructed. 15 The unit cell structure models are denoted as KSN-O, KSN-K&O, KSN-Sr&O, KSN-Nb1&O, and KSN-Nb2&O; Step 3, using VASPKIT software to perform convergence tests on the KSN obtained in step 1 and the KSN-O, KSN-K&O, KSN-Sr&O, KSN-Nb1&O and KSN-Nb2&O obtained in step 2, respectively, to determine the calculation parameters when the system reaches convergence; Step 4, based on the calculation parameters when the system reaches convergence in step 3, use CASTEP software to optimize the KSN obtained in step 1 and the KSN-O, KSN-K&O, KSN-Sr&O, KSN-Nb1&O and KSN-Nb2&O unit cell structures obtained in step 2, respectively, so as to achieve the lowest energy of the system and obtain the most stable unit cell structure; Step 5, using CASTEP software to calculate the optical frequency dielectric constants of the most stable KSN, KSN-O, KSN-K&O, KSN-Sr&O, KSN-Nb1&O and KSN-Nb2&O unit cell structures in step 4 respectively; Step 6, based on the Clausius-Mossotti equation, calculate the ionic polarizabilities of the most stable KSN, KSN-O, KSN-K&O, KSN-Sr&O, KSN-Nb1&O and KSN-Nb2&O unit cell structures in step 4 respectively; Step 7, calculating the spontaneous polarization intensity range of the KSN unit cell structure according to the ionic polarizability of the KSN unit cell structure obtained in step 6; Step 8, according to step 7, the spontaneous polarization intensity range of KSN is obtained, the built-in electric field range is calculated, and then according to the relationship between the spontaneous polarization intensity and the built-in electric field, the spontaneous polarization intensity of the most stable KSN-O, KSN-K&O, KSN-Sr&O, KSN-Nb1&O and KSN-Nb2&O unit cell structures in step 4 is obtained; Step 9: Based on the spontaneous polarization intensity ranges of the KSN-O, KSN-K&O, KSN-Sr&O, KSN-Nb1&O and KSN-Nb2&O unit cell structures obtained in step 8, potassium strontium niobate ceramics with high spontaneous polarization intensity are screened out.

2. The method for screening potassium strontium niobate with high spontaneous polarization intensity according to claim 1, characterized in that: In step 2, KSr2Nb5O with oxygen vacancies, cation vacancies and oxygen vacancies at site A, and cation vacancies and oxygen vacancies at site B is constructed. 15 The unit cell structure model process is as follows: Delete KSr2Nb5O 15 One O atom in the unit cell structure corresponds to a vacancy concentration of 2.17 atom%, resulting in K2Sr4Nb 10 O 29 The unit cell structure is denoted as KSN-O; Delete KSr2Nb5O 15 There is one K atom and one O atom in the unit cell structure, and the corresponding vacancy concentration is 4.35 atom%, resulting in KSr4Nb 10 O 29 The unit cell structure is denoted as KSN-K&O; Delete KSr2Nb5O 15 There is one Sr atom and one O atom in the unit cell structure, and the corresponding vacancy concentration is 4.35atom%, resulting in K2Sr3Nb 10 O 29 The unit cell structure is denoted as KSN-Sr&O; Delete KSr2Nb5O 15 The Nb atoms and O atoms located at the Nb1 position in the unit cell structure have a corresponding vacancy concentration of 4.35 atom%, resulting in K2Sr4Nb9O 29 The unit cell structure is denoted as KSN-Nb1&O; Delete KSr2Nb5O 15 The Nb atoms and O atoms located at the Nb2 position in the unit cell structure have a corresponding vacancy concentration of 4.35 atom%, resulting in K2Sr4Nb9O 29 The unit cell structure is denoted as KSN-Nb2&O.

3. The method for screening potassium strontium niobate with high spontaneous polarization intensity according to claim 1, characterized in that: In step 3, the PBE pseudopotential library is used in the VASPKIT software to perform convergence tests on the KSN obtained in step 1 and the KSN-O, KSN-K&O, KSN-Sr&O, KSN-Nb1&O, and KSN-Nb2&O obtained in step 2, and the cutoff energy is determined to be 750 eV, the k-point is 6×6×6, and the energy convergence standard is 4.0×10 -5 eV, the convergence criterion for the force is that a single atom is below The maximum displacement is 4. The method for screening potassium strontium niobate with high spontaneous polarization intensity according to claim 1, characterized in that: The process of calculating the ion polarizability based on the Clausius-Mossotti equation in step 6 is as follows: The expression of the Clausius-Mossotti equation is as follows: Among them, ε r represents the relative dielectric constant, ε0 represents the vacuum dielectric constant, 8.85×10 -12 F / m, α represents the ionic polarizability, and n0 represents the number of polarized particles per unit volume of the dielectric; If the volume is replaced by the molar volume M / ρ, then: Where N0 is Avogadro's constant, in mol -1 , M represents the molar mass of the dielectric, and ρ represents the density; because Where V is the unit cell volume; Substituting formula (3) into the transformation of formula (2): get: At optical frequencies, the relative dielectric constant ε of a dielectric is r Available optical frequency dielectric constant ε ∞ To express, at this time, formula (1) can be expressed as: According to the optical frequency dielectric constant ε calculated from the first principles in step 5 ∞ , the product n0α of the number of polarized particles n0 per unit volume of the material and the ionic polarizability α is calculated using formula (5); and the number of polarized particles n0 per unit volume is obtained by formula (4), and then the ionic polarizability α is obtained.

5. The method for screening potassium strontium niobate with high spontaneous polarization intensity according to claim 1, characterized in that: The process of calculating the spontaneous polarization intensity range of the KSN unit cell structure in step 7 is as follows: Step 7.1: Calculate the dipole moment of KSN by experimental method and first principles, namely: Method 1: Calculate the dipole moment of KSN according to the experimental method: Curie temperature T of KSN obtained by experimental method c , get Nb in KSN 5+ The offset △z of KSN is obtained, and then the dipole moment of KSN is obtained; The displacement △z of the cation offset charge center in the displacement type ferroelectric unit cell is related to the Curie temperature T c The relationship is as follows: T C =2×10 4 (Δz) 2 (6) Among them, T c Represents Curie temperature, in K; The relationship between the displacement △z of the cation offset charge center in the displacement-type ferroelectric unit cell and the dipole moment of KSN is as follows: m KSN =nqΔz (7) Among them, μ KSN represents the dipole moment of KSN, in C·m; n represents the number of atoms; q represents the unit charge, 1.6×10 - 19 C; Method 2: Calculate the dipole moment of KSN based on first principles: The most stable KSN unit cell structure obtained in step 4 is input into the VASP software to obtain the average distance l between positive and negative charges. The dipole moment of KSN is calculated based on the first principles, and the expression is as follows: μ KSN =ngl (8) Among them, μ KSN represents the dipole moment of KSN, in C·m; n represents the number of atoms; l represents the average distance between positive and negative charges; q represents the unit charge, 1.6×10 -19 C; Step 7.2: Calculate the spontaneous polarization intensity range of KSN based on the dipole moment of KSN obtained in step 7.1; The two expressions of the spontaneous polarization intensity are as follows: Where μ represents the dipole moment and V represents the unit cell volume; P=n0μ=n0αE e (10) Where n0 represents the number of polarized particles per unit volume of the dielectric; μ represents the dipole moment; α represents the ionic polarizability; E e represents the built-in electric field; Substitute the dipole moment of KSN obtained by experimental method and first-principles calculation in step 7.1 into equations (9) and (10) respectively to obtain the spontaneous polarization intensity range of KSN.

6. The method for screening potassium strontium niobate with high spontaneous polarization intensity according to claim 1, characterized in that: The chemical composition of potassium strontium niobate ceramics with high spontaneous polarization intensity selected in step 9 is: K2Sr4Nb 10 O 29 、KSr4Nb 10 O 29 and K2Sr4Nb9O 29 .

Citation Information

Patent Citations

  • Method for preparing acicular strontium postasium noobate microcrystalline powder

    CN102616852A

  • Preparation method of cylindrical strontium sodium niobate crystallite powder

    CN102863024A

  • Lead-free compact strontium postasium niobate textured ceramic and preparation method thereof

    CN103420673A

  • Preparation method for simulating and regulating grain size of ferroelectric textured ceramic by using phase field method

    CN115458089A

  • Strontium potassium niobate ceramic with high thermoelectric performance and construction method thereof

    CN116813345A

Cited By

  • Calculation method for obtaining ferroelectric material with high polarizability

    CN121393674A